Decontamination of industrial textile wastewater using photocatalysis (2016)
Iron-doped TiO2 catalysts were prepared by impregnation in order to study their photocatalytic activity in the treatment of wastewater from the textile industry. Characterization of the catalysts before and after reaction was performed using techniques including total surface area measurement, X-Ray diffraction and elemental analysis via X-Ray fluorescence. Varying pH conditions, H2O2 concentrations and catalyst quantities were evaluated during the photocatalytic reactions. Fe-TiO2 catalysts were shown to be highly active in the reduction of chemical oxygen demand and Color reduction in the water treated.